Impact of Vitamin D and IL-1β on Quality of Life in Pediatric Drug-Resistant Epilepsy - Saing JH; Sari DK; Supriatmo; Fitri A; Pratama MA (Journal of Multidisciplinary Healthcare)
Johannes Harlan Saing,1 Dina Keumala Sari,2 Supriatmo,1 Aida Fitri,3 Muhammad Arief Pratama4 1Department of Pediatrics, Faculty of Medicine, Universitas Sumatera Utara, Medan, North Sumatra, Indonesia; 2Department of Nutrition, Faculty of Medicine, Universitas Sumatera Utara, Medan, North Sumatra, Indonesia; 3Department of Neurology, Faculty of Medicine, Universitas Sumatera Utara, Medan, North Sumatra, Indonesia; 4Department of Clinical Pathology, Faculty of Medicine, Universitas Sumatera Utara, Medan, North Sumatra, IndonesiaCorrespondence: Dina Keumala Sari, Department of Clinical Nutrition, Faculty of Medicine, Universitas Sumatera Utara, Jl. Dr. Mansur, No. 5, Kampus USU, Padang Bulan, Medan, Indonesia, Tel +6281397177693, Email dina@usu.ac.idBackground: Epilepsy is highly prevalent among children worldwide, making it one of the most common neurological disorders. Drug-Resistant Epilepsy (DRE) significantly impacts the quality of life (QoL) of affected children, attributed to factors such as seizure frequency and severity, low vitamin D levels, comorbidities, radiological abnormalities, and elevated IL-1β levels.Objective: This study aims to identify the factors most significantly affecting the QoL in children with DRE.Methods: This cross-sectional study at Adam Malik Hospital involved children with DRE. Participants’ QoL was assessed with the QOLCE-55 score, while epilepsy severity was measured using the HASS score. Vitamin D status was quantified by serum 25-hydroxy vitamin D (25(OH)D) levels, and IL-1β levels were measured using the ELISA method. Multivariate logistic regression analysis using Pearson and Spearman test was conducted to evaluate risk factors that significantly impact the QoL of children with DRE.Results: The findings revealed several factors significantly influencing QoL in children with DRE. Comorbidities (OR = 24.98, p = 0.004, 95% CI) and high IL-1β levels (OR = 8.36, p = 0.022, 95% CI) were strongly correlated and significant factors in determining QoL, indicating 24.98- and 8.36-times higher likelihood of decreased QoL, respectively. Vitamin D levels had no statistically significant effect on QoL.Conclusion: Vitamin D levels have no substantial impact on QoL in children with DRE. IL-1β levels and comorbidities are crucial components affecting QoL in these patients. These findings highlight the importance of considering these factors in the management of children with DRE.Keywords: vitamin D, interleukin-1 beta, comorbidities, quality of life, drug-resistant epilepsy